2008
DOI: 10.1021/la8006316
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Lithium Ions in MgO Lattice: Surface Characterization by Infrared Spectroscopy and Reactivity towards Oxidative Conversion of Propane

Abstract: The surface morphology of Li-promoted MgO catalysts prepared using the sol-gel method (sg) and wet impregnation procedure (imp), respectively, has been studied by low-temperature infrared spectroscopy of adsorbed CO molecules. The results show that step sites, as unselective catalytic centers, are the major features existing on the surface of pure MgO, and those are active toward the oxidative conversion of propane. However, the concentration of these sites is drastically reduced by the incorporation of lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…The catalyst showed very good selectivity to C 2 -C 4 olefins (60 mol %) at a temperature as low as 575°C, which is much lower than temperatures used in steam crackers (T C 800°C). Similar to what is reported in literature and our earlier studies for oxidative conversion of lower alkanes (methane [3], ethane [4][5][6]12], propane [6][7][8][9][10][11] and butane [7]), we proposed hexane activation via the [Li ? O -] sites of Li/MgO abstracting H • . The hexyl radical formed then undergoes complex radical chemistry in gas phase in presence of molecular oxygen, forming the product mixture of C 1 -C 5 products, including olefins, paraffins and combustion (CO x ) products.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The catalyst showed very good selectivity to C 2 -C 4 olefins (60 mol %) at a temperature as low as 575°C, which is much lower than temperatures used in steam crackers (T C 800°C). Similar to what is reported in literature and our earlier studies for oxidative conversion of lower alkanes (methane [3], ethane [4][5][6]12], propane [6][7][8][9][10][11] and butane [7]), we proposed hexane activation via the [Li ? O -] sites of Li/MgO abstracting H • . The hexyl radical formed then undergoes complex radical chemistry in gas phase in presence of molecular oxygen, forming the product mixture of C 1 -C 5 products, including olefins, paraffins and combustion (CO x ) products.…”
Section: Introductionsupporting
confidence: 82%
“…The existence of CH and H bands in the optical emission spectrum of C 6 H 14 -He mixture indicate the decomposition of hexane in plasma via C-H and C-C bond cleavage. CH • radicals in the presence of plasma are generally formed, as proposed in literature by Kado et al [22], through the extensive dehydrogenation of methyl radicals via multiple electron impact excitations (9-10) and/or from the coupling of atomic C and H radical (11) formed through extensive dissociation of methane (12). 3 Optical emission spectrum for a gas mixture of 10% hexane in helium in the presence of plasma at 3 W and at ambient conditions.…”
Section: Oxidative Conversion Of Hexane In the Presence Of Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Computational studies indicate that CO coordination via carbon only in form of a bridged complex is more likely [14]. Trionfetti et al observed this band also after CO adsorption on Li/MgO catalysts, but with increasing Li content, the contribution of the step sites decreases [15], which is in agreement of the ''ironing'' effect of alkali additives [16].…”
Section: Resultssupporting
confidence: 50%
“…This observation is consistent with the findings of Spoto et al [2] who argued that CO is adsorbed to pairs of Mg 2+ cations at low pressures in bridged configuration, while at higher pressure, this configuration is displaced by a 1:1 ratio between Mg 2+ centers and adsorbed CO. Features located in the range between 2180 and 2160 cm À1 are typically assigned to terminal CO adsorbed on Mg 2+ 4C centers [2,15], which occur at the surface as edges of either mono-atomic or multi-atomic steps, respectively. We therefore assign the band located at 2164 cm À1 in Fig.…”
Section: Resultsmentioning
confidence: 99%